Oscillation Theorems for Second-Order Nonlinear Neutral Delay Differential Equations - Tongxing Li; Yuriy V. Rogovchenko (Abstract and Applied Analysis)
We analyze the oscillatory behavior of solutions to a class of second-order nonlinear neutral delay differential equations. Our theorems improve a number of related results reported in the literature.